Predictors for pathological parametrial invasion in clinical stage IIB cervical cancer. Issue 8 (August 2019) - Matsuo, Koji; Shimada, Muneaki; Nakamura, Keiichiro; Takei, Yuji; Ushijima, Kimio; Sumi, Toshiyuki; Ohara, Tatsuru; Yahata, Hideaki; Mikami, Mikio; Sugiyama, Toru
Abstract: Objective: To examine predictors of pathological parametrial invasion in clinical stage IIB cervical cancer, and to examine prognostic factors in pathological stage IIB disease. Methods: This study is an ancillary analysis of a nation-wide retrospective cohort examining 6, 003 clinical stage IB-IIB cervical cancers. Women with clinical stage IIB disease who underwent primary radical hysterectomy with lymphadenectomy were examined ( n = 714). Multivariate analysis was performed to identify independent clinico-pathological factors for pathological parametrial invasion and to identify independent prognostic factors in pathological stage IIB disease. Results: Parametrial invasion was identified on the surgical specimen in 400 cases (56.0%, 95% confidence interval 52.4–59.7). On multivariate analysis, deep stromal invasion (DSI, adjusted-OR 3.922), multiple pelvic nodal metastases (adjusted-OR 3.266), lympho-vascular space invasion (adjusted-OR 2.333), and uterine corpus invasion (adjusted-OR 1.656) remained independent tumor factors for pathological parametrial invasion. In classification-tree models, tumors with DSI and multiple pelvic nodal metastases had the highest incidence of pathological parametrial invasion (75.0–87.7%); contrary, tumors without DSI had the lowest incidence (21.9%). Among patients with pathological stage IIB disease, the absolute difference in 5-year disease-free survival rates was 57.2%, ranging between 80.9% in those with squamous histology with none/single pelvic nodal metastasis and 23.7% in those with non-squamous histology with multiple pelvic nodal metastases. Conclusion: In clinical stage IIB cervical cancer, accuracy for pathological parametrial invasion is low-modest. With absence of DSI, only one in five clinical stage IIB diseases has pathological stage IIB disease. Survival of pathological stage IIB varies widely and is largely dependent on nodal factors.